Knowledge, attitude and preventive practices regarding tuberculosis care and control among health care professionals at TB centres: implications for TB control efforts - Jaiswal, K. M.; Vaishnao, Lohit S.; Dudhgaonkar, Sujata; Raghte, Latesh; Kewalramani, Mahek S.; Jawade, Ashutosh S.; Chugh, Kunal C. (International Journal Of Community Medicine And Public Health, 2020)
Background: Tuberculosis (TB) ranks as the leading cause of death from infectious disease. The World Health Organization (WHO) has considered TB a global public health disaster since 1993. Four factors affect non-adherence to treatment-the patient, healthcare systems, pharmaco-therapeutics and the key persons, health care professional (HCP). So, the study was conducted to evaluate knowledge, attitudes and practices regarding TB care and control in HCPs working in TB units. Methods: This was a cross-sectional, observational, questionnaire-based study conducted in all the HCPs working for the TB care and control. Results: The responses to the questions of knowledge were variable indicating incompleteness of information, facts, understanding related to TB in HCPs. HCPs show very strong positive attitude for finding every new case of TB is essential. The HCPs disagree to some statements like traditional or alternative medicine assists in wellbeing of TB patients. Practice competency was low with average score 2.32 out of 6, doctors having higher score of 4.62 followed by nurses, lab-technicians, pharmacist and activist with score of 2.57, 1.66, 1.5, 1.25 respectively. The activist are the key persons in the national tuberculosis program, exhibited the least score in this study indicates they do not have much orientation about the practice of TB treatment. Specific deficiencies existed for some knowledge statements of HCWs on TB. There was disagreement in attitudes regarding stigma and traditional medicine, and practice competencies were poor. Improvement in aspect of KAP of HCPs on TB will help India achieve the goal of End TB. Conclusions: Specific deficiencies existed for some knowledge statements of TB in paramedical staff as compared to doctor participants. There was disagreement in attitudes regarding stigma and traditional medicine, and practice competencies were poor in activists. Improvement in knowledge, attitude and practices of TB in paramedical staff by conducting CME, Workshop, training sessions will help India to achieve the goal of End TB.